Effect of hot aqueous extract of seeds and leaves of fenugreek (Trigonella foenum-graecum) on embryonic development in swiss albino mice (Baghdad Science Journal, 2017)
The present study has conducted to investigate the effect of hot aqueous extract of seeds and leaves of fenugreek (Trigonella foenum-graecum) on embryonic development in Swiss albino mice morphologically , the results is showed throught dosage pregnant female orally after period 4, 8, 12days at the beginning of pregnancy by doses 100 , 200 , 300 mg/kg of body weight , the results showed normal period of pregnancy 21 days and abortion did not occur when the pregnant mice take the hot aqueous extract of leaves of fenugreek, but the pregnant mice that take the hot aqueous extract of seeds of fenugreek occurred abortion of embryos and showed some histopathological changes in ovaries and uterus such as congestion, hemorrhage, necrosis, odema, no morphological malformations observed in embryos.